2000
DOI: 10.3171/jns.2000.93.6.1026
|View full text |Cite
|
Sign up to set email alerts
|

GFP labelled ES cell derived neural precursor cells differentiate into Thy-1 positive neurons and glia after transplantation into the striatum of the adult rat striatum

Abstract: The investigators found that after transplantation, a subpopulation of GFP-labeled cells differentiated into various neural morphological types that were positive for the mouse-specific Thy-1 antigen, which is known be expressed on neurons, as well as being positive for the astroglial marker glial fibrillary acidic protein. Moreover, GFP-expressing cells that were negative for either of these markers remained close to the injection site, presumably representing other derivatives of the neural lineage. Together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 30 publications
(37 reference statements)
1
53
0
Order By: Relevance
“…Murine ES cells of the D3 cell line, stably transfected with the pCX-(␤-act)-EGFP expression vector (Arnhold et al, 2000), were cultivated in Dulbecco modified Eagle medium (DMEM) containing 15% fetal calf serum (FCS), nonessential amino acids (stock solution 1:100), penicillin-streptomycin (stock solution 1:100), 50-mol/L ␤-mercaptoethanol, and 100-nmol/L leukemia-inhibiting factor (Williams et al, 1988). For in vitro predifferentiation of ES cells, hanging drops were established by plating a suspension of 200 ES cells in 20 L DMEM plus 10% FCS with leukemia-inhibiting factor on the lids of bacterial dishes.…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine ES cells of the D3 cell line, stably transfected with the pCX-(␤-act)-EGFP expression vector (Arnhold et al, 2000), were cultivated in Dulbecco modified Eagle medium (DMEM) containing 15% fetal calf serum (FCS), nonessential amino acids (stock solution 1:100), penicillin-streptomycin (stock solution 1:100), 50-mol/L ␤-mercaptoethanol, and 100-nmol/L leukemia-inhibiting factor (Williams et al, 1988). For in vitro predifferentiation of ES cells, hanging drops were established by plating a suspension of 200 ES cells in 20 L DMEM plus 10% FCS with leukemia-inhibiting factor on the lids of bacterial dishes.…”
Section: Cell Culturesmentioning
confidence: 99%
“…It has been shown that transplantation of undifferentiated ES cells into the intact animal produces teratomas or even highly malignant teratocarcinomas (Reubinoff et al, 2000;Thomson et al, 1998), but the tumorigenic potential of ES cells seems to be greatly reduced when cells are predifferentiated in vitro before implantation. Successful examples of this approach include intracerebral implantations of ES cell-derived neural, neuronal, or glial progenitor cells, all of which did not produce brain tumors (Arnhold et al, 2000;Brüstle et al, 1999;Reubinoff et al, 2001;Zhang et al, 2001). Obviously, in vitro differentiation by currently applied protocols does not fully prevent the persistence of some undifferentiated cells, but this fraction does not seem to build up the oncogenic potential required for the induction of tumor growth (Reubinoff et al, 2001;Zhang et al, 2001).…”
mentioning
confidence: 99%
“…ES cell differentiation has also been discussed as an experimental avenue to generate cells for transplantation. ES-cell-derived cardiomyocytes, neuronal cells and insulin-secreting cells have been transplanted into animals and were able to integrate specifically (Klug et al, 1996;Brüstle et al, 1999;McDonald et al, 1999;Arnhold et al, 2000;Liu et al, 2000;Soria et al, 2000). Because ES cells differentiate spontaneously into a heterogeneous population of cells, it is necessary to use selection strategies to obtain pure cultures of a specific cell type.…”
mentioning
confidence: 99%
“…This technique is particularly useful for tracking stem or progenitor cells in vivo, as these cells tend to migrate and differentiate based on the cellular environment within the transplanted area of the host. [37][38][39] Stem cells labeled by transfection with GFP or other markers have been transplanted into various animal models of human pathological conditions, such as Parkinson's disease, 40 retinal dystrophy, 41 and ischemic stroke. 42 Hence, there is a question of whether the transfection affects the overall integrity of the genome expression, as expression of GFP in cardiomyocytes was shown to affect several metabolic and signaling pathways but did not affect cell viability.…”
Section: Gfp Transgenic Pbpcs Have Similar Genetic Expression To Non-mentioning
confidence: 99%